Adherence to Methotrexate in Rheumatoid Arthritis: A Danish Nationwide Cohort Study. (25th February 2015) - Bliddal, Henning; Eriksen, Stine A.; Christensen, Robin; Lorenzen, Tove; Hansen, Michael S.; Østergaard, Mikkel; Dreyer, Lene; Luta, George; Vestergaard, Peter
Abstract : Objectives . To study adherence to methotrexate (MTX) and factors of importance thereof in patients with rheumatoid arthritis (RA). Methods . Patients with a hospital diagnosis of RA (ICD10 codes M05.X or M06.X) after January 1, 1997, and aged ≥18 years at the date of first diagnosis/contact, with at least one prescription of MTX (L04AX03), were included. Results . A total of 18, 703 (47.6%) patients had ever used MTX among 39, 286 with a diagnosis of RA; among the MTX users, 16, 503 (88.2%) had filed more than one MTX prescription. The median time from diagnosis to first MTX prescription was 0.66 (IQR 0.26–1.80) years. In those who filed more than one MTX prescription, the mean adherence time for ≥7.5 mg MTX per week was 1, 925 (IQR 467–3, 056) days for patients treated in private practice versus 1, 892 (IQR 452–3, 316) days for patients treated in hospital. The main determinants of nonadherence were female gender, younger age, and time from diagnosis to initiation of MTX. Conclusions . Treatment at hospital or in private practice did not influence the adherence to MTX. Nonmodifiable factors of importance were gender and age, while adherence to MTX therapy decreased with time lapse between diagnosis and prescription.